2014
DOI: 10.1109/ted.2014.2337713
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Modeling of the Carrier Mobility in FDSOI Devices

Abstract: We compute the electron and hole mobilities in ultrathin body and buried oxide, fully depleted silicon on insulator devices with various high-κ metal gate-stacks using nonequilibrium Green's functions (NEGF). We compare our results with experimental data at different back gate biases and temperatures. That way, we are able to deembed the different contributions to the carrier mobility in the films (phonons, front and back interface roughness, and remote Coulomb scattering). We discuss the role played by each m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…C EPS is a numerical fitting factor, which is adjusted to a value such that the model accounts for the correct value of the electron mobility. 32 The relation between C EPS and mobility is shown in Table 2. Electron mobility in hybrid perovskites has been experimentally measured from 1 to 100 cm 2 /(V s).…”
Section: Methodsmentioning
confidence: 99%
“…C EPS is a numerical fitting factor, which is adjusted to a value such that the model accounts for the correct value of the electron mobility. 32 The relation between C EPS and mobility is shown in Table 2. Electron mobility in hybrid perovskites has been experimentally measured from 1 to 100 cm 2 /(V s).…”
Section: Methodsmentioning
confidence: 99%
“…[33]. We use a diagonal hole-phonon interaction with one single acoustic deformation potential D ac = 16.5 eV and one single optical deformation potential DK opt = 15 eV/Å [34]. Details about the NEGF implementation can be found in Ref.…”
Section: Devices and Methodologymentioning
confidence: 99%
“…The total mobility µ can be reconstructed from the partial PH, SR and RCS mobilities with Matthiessen's rule. Since µ SR ∝ 1/∆ 2 SR [31], [32] and µ RCS ∝ 1/n RCS [39], [40], µ can be written for arbitrary ∆ SR and n RCS [34]:…”
Section: Carrier Mobilities In Square Nanowires and Thin Filmsmentioning
confidence: 99%
“…However, the effective mass approximation in concomitance with scattering has been shown to reproduce experimental results. 38,39 Also, we previously demonstrated that for Si NWFETs, our own effective mass model reproduces the mobility of TB simulations. 30 The phonon limited mobility can be calculated using…”
Section: Simulation Methodologymentioning
confidence: 55%